First molecular evidence of Babesia caballi and Theileria equi infections in horses in Cuba - Díaz-Sánchez, Adrian Alberto; Pires, Marcus Sandes; Estrada, Carlos Yrurzun; Cañizares, Ernesto Vega; del Castillo Domínguez, Sergio Luis; Cabezas-Cruz, Alejandro; Rivero, Evelyn Lobo; da Fonseca, Adivaldo Henrique; Massard, Carlos Luiz; Corona-González, Belkis (Parasitology research (1987), 2018)
Equine piroplasmosis is a disease of Equidae, including horses, donkeys, mules, and zebras, caused by either Theileria equi or Babesia caballi . This disease represents a serious problem for the horse industry and its control is critical for the international trade of horses. The objective of the present study was to detect B. caballi and T. equi infections in horses reared in western Cuba. Blood samples from 100 horses were tested for the presence of piroplasms by using Giemsa-stained blood smears and nested PCR (nPCR) assays targeting merozoite antigen genes of B. caballi ( bc 48) and T. equi ( ema -1). All animals were inspected for the detection of tick infestation and tick specimens were collected for species identification. Erythrocyte inclusions were observed in 13 (13%) of the analyzed samples. nPCR analysis showed that 25 (25%) samples were positive for B. caballi , 73 (73%) for T. equi , and 20 (20%) showed dual infections. Only one tick species was found infesting horses, Dermacentor nitens . In addition, three nearly full-length sequences of T. equi 18S rRNA gene were obtained and subjected to phylogenetic analyses. This study reports a high prevalence of T. equi and B. caballi single and coinfections in horses in western Cuba. Molecular analysis of the 18S rRNA gene of T. equi suggested that different genotypes of this hemoparasite circulate in Cuba. To the best of our knowledge, this is the first report describing the molecular detection of B. caballi and T. equi in horses in Cuba.